Iron dextran and farbegen compared as methods of preventing iron deficiency anemia in neonatal pigs - Schoneweis, D.A.; Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The experiment suggests that a primary need of the neonatal pig is iron and that hematinics such as cobalt and liver extract are of little value if iron is insufficient.
Bright Future? is known as Swine Day, 1977
Keywords: Swine; Iron dextran; Farbegen; Iron deficiency anemia; Neonatal pigs